2022
DOI: 10.1371/journal.pone.0271977
|View full text |Cite
|
Sign up to set email alerts
|

Identity, trust, and the experiences of refugees during a COVID-19 lockdown

Abstract: This paper examines the experiences of refugees in a developing country during its first COVID-19 lockdown by utilizing a two-stage qualitative data analysis of 39 interviews with refugees and asylum-seekers. We find that their experiences during the lockdown are shaped by identity, trauma and help from external parties–such as community leaders and local non-governmental organizations (NGOs). Experiences during the pandemic in turn moderate the relationship between policy changes and trust in domestic authori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Then, a mixed-method study showed a high prevalence of exposure to COVID-19, poor mental health, and frequent avoidance of healthcare among undocumented migrants [ 9 ]. Similarly, a qualitative study described the social and economic burden of the COVID-19 pandemic experienced by migrant populations [ 21 ]. Regarding the perception of migrant populations towards public health measures, such as lockdowns, our study confirms the ambivalent feelings also observed in shelters in France.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, a mixed-method study showed a high prevalence of exposure to COVID-19, poor mental health, and frequent avoidance of healthcare among undocumented migrants [ 9 ]. Similarly, a qualitative study described the social and economic burden of the COVID-19 pandemic experienced by migrant populations [ 21 ]. Regarding the perception of migrant populations towards public health measures, such as lockdowns, our study confirms the ambivalent feelings also observed in shelters in France.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, asylum seekers with limited awareness or a lack of understanding of public health recommendations due to inadequate communication and language or cultural barriers may have experienced more worries about the COVID-19 pandemic (fear of being infected or dying) and greater mental health deterioration [ 20 , 21 ]. Previous literature has indeed identified inequities surrounding communication during pandemics, affecting linguistic minorities and socially excluded.…”
Section: Introductionmentioning
confidence: 99%